Effect of Months and Season on Some Blood Plasma Constituencies of She-camels from Parturition tone Year After Under Laybian Grazing Conditions - ِAl- Taif, Tarek Abdo-Alslam Salem (Al-Mukhtar Journal of Sciences, 2008)
The study was carried – out in middle – Libyan country; El-Hisha reqion, on three she-camels under desert grazing to investigate the effects of season and months on some blood plasma constituents. Blood samples were taken monthly except March and December. Blood urea concentration was increased during spring, summer and at parturition then decreased followed by increasing at the tenth month. Creatinine was increased (p < 0.05) during spring and autumn but, decreased at parturition and the following month. Protein concentration was increased (p < 0.05) during summer, However decreased at parturition and following month and reached a peak level at the fifth month. Glucose was increased (p < 0.05) during winter and at parturition. Sodium ions were increased (p < 0.05) during summer and the fifth month. Potassium ions were increased (p < 0.05) during autumn but, decreased at parturition and the consequent month.